Logistyczne strategie rozwoju przedsiębiorstw CARGO sektora transportu kolejowego na wspólnym liberalizowanym rynku transportowym na przykładzie PKP CARGO SA - Antonowicz, Mirosław (Logistic Strategies of Development of CARGO Undertakings in the Rail Transport Sector on the Common Liberalizing Transport Market in UE on Example of PKP CARGO SA CASE, 2005)
In the paper the author presented the main factors of the competitive advantages of undertakings in transport sector and strategic solutions in the sector. He described in synthetic way the reasons of redefinition of hitherto existing strategic rules of companies activities in this sector. He indicated the role and importance of logistics for development of rail transport companies. He presented in draft the size of logistic activities of PKP CARGO SA.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 193-202